Management Therapy in Chronic Ectopic Pregnancy - Pradana, Aryando (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: Improving skill in making a diagnosis and management therapy in chronic ectopic pregnancy. Method: Case Report. Conclusion: Diagnosis of chronic EP is difficult to establish before surgery. Conservative treatment using medication (methotrexate) can not be applied to chronic EP because the Î²-hCG level is difficult to be detected. [Indones J Obstet Gynecol 2010; 34-4: 199-203] Keywords: ectopic pregnancy, chronic ectopic pregnancy